2009
DOI: 10.1055/s-0029-1210810
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation Induction for In-Vitro-Fertilization and Embryo Transfer Applying Decapeptyl (DTRP-6 LH/RH) in Combination with HMG or FSH

Abstract: 47 patients out of the IVF-program of the Department of Obstetrics and Gynecology University of Kiel, who demonstrated in previous stimulation cycles premature LH surges, were treated in two modalities with a down regulation applying the GnRN-analogue decapeptyl (DTRP-6 LH/RH) and a concomitant HMG- or FSH-stimulation. The down-regulation was started after ovulation up to a negative LH/RH test followed by a concomitant gonadotropin stimulation in group 1. In group 2 a parallel treatment with decapeptyl and HMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…One initial complication of COH treatments was the presence of premature LH surges resulting in poor IVF outcome [5]. Multiple authors [6,7] have shown the benefits of GnRH-a use in preventing a premature LH surge in IVF. Yet, such therapy requires long duration (4 weeks) of administration and when the intranasal route is used, strict time keeping (6 hourly) with subsequent interference with normal life patterns.…”
Section: Discussionmentioning
confidence: 99%
“…One initial complication of COH treatments was the presence of premature LH surges resulting in poor IVF outcome [5]. Multiple authors [6,7] have shown the benefits of GnRH-a use in preventing a premature LH surge in IVF. Yet, such therapy requires long duration (4 weeks) of administration and when the intranasal route is used, strict time keeping (6 hourly) with subsequent interference with normal life patterns.…”
Section: Discussionmentioning
confidence: 99%